Comparison of community-wide, integrated mass drug administration strategies for schistosomiasis and soil-transmitted helminthiasis: a cost-effectiveness modelling study. Issue 10 (October 2015) - Lo, Nathan C; Bogoch, Isaac I; Blackburn, Brian G; Raso, Giovanna; N'Goran, Eliézer K; Coulibaly, Jean T; Becker, Sören L; Abrams, Howard B; Utzinger, Jürg; Andrews, Jason R
Summary: Background: More than 1·5 billion people are affected by schistosomiasis or soil-transmitted helminthiasis. WHO's recommendations for mass drug administration (MDA) against these parasitic infections emphasise treatment of school-aged children, using separate treatment guidelines for these two helminthiases groups. We aimed to evaluate the cost-effectiveness of expanding integrated MDA to the entire community in four settings in Côte d'Ivoire. Methods: We extended previously published, dynamic, age-structured models of helminthiases transmission to simulate costs and disability averted with integrated MDA (of praziquantel and albendazole) for schistosomiasis and soil-transmitted helminthiasis. We calibrated the model to data for prevalence and intensity of species-specific helminth infection from surveys undertaken in four communities in Côte d'Ivoire between March, 1997, and September, 2010. We simulated a 15-year treatment programme with 75% coverage in only school-aged children; school-aged children and preschool-aged children; adults; and the entire community. Treatment costs were estimated at US0·74 for school-aged children and 1·74 for preschool-aged children and adults. The incremental cost-effectiveness ratio (ICER) was calculated in 2014 US dollars per disability-adjusted life-year (DALY) averted. Findings: Expanded community-wide treatment was highly cost effective compared with treatment of only school-aged children (ICER 167 per DALY averted) and WHO guidelines (ICER 127 per DALY averted), and remained highly cost effective even if treatment costs for preschool-aged children and adults were ten times greater than those for school-aged children. Community-wide treatment remained highly cost effective even when elimination of helminth infections was not achieved. These findings were robust across the four diverse communities in Côte d'Ivoire, only one of which would have received annual MDA for both schistosomiasis and soil-transmitted helminthiasis under the latest WHO guidelines. Treatment every 6 months was also highly cost effective in three out of four communities. Interpretation: Integrated, community-wide MDA programmes for schistosomiasis and soil-transmitted helminthiasis can be highly cost effective, even in communities with low disease burden in any helminth group. These results support an urgent need to re-evaluate current global guidelines for helminthiases control programmes to include community-wide treatment, increased treatment frequency, and consideration for lowered prevalence thresholds for integrated treatment. Funding: Stanford University Medical Scholars Programme, Mount Sinai Hospital-University Health Network AMO Innovation Fund.